(untitled) (Journal of Universal Science Research, 2023)
In the modern world, there is a fairly large amount of information flow that surrounds us everywhere and we are faced with the need for early learning of information technologies and computer science from the initial stage of training. Every teacher should use all opportunities to ensure that children learn with interest, understand and experience the attractive aspects of computer science, its possibilities in improving mental abilities, in overcoming difficulties. The use of non-traditional, non-standard forms of education, in particular game technologies, has a beneficial effect on the educational process.